When green energy feels cozy: The interplay of protected values, the halo effect, and demographics in consumers’ renewable energies adoption - Juan Pablo Loaiza-Ramírez; Torsten Reimer; Carlos Eduardo Moreno-Mantilla (Cleaner and Responsible Consumption)
Adopting renewable energies at the individual level is required to mitigate greenhouse gas emissions, reduce reliance on fossil fuels, and transition to a society based on green energy. This study taps into this topic by exploring why and which consumers would adopt renewable energies using two psychological approaches (i.e., protected values and the halo effect) and by looking at the role of consumers’ demographics in their willingness to pay for renewable energy. Evidence of a comfort halo effect was found for consumers with high protected values (i.e., with a moral orientation toward the environment) using two-instance repeated-measures linear regressions in an MTurk experiment: Those consumers are likely to perceive more comfort at home when they know their electricity is sourced from renewable energies. This effect does not hold for consumers who have low protected values. Consumers with high protected values were not willing to pay more for renewable energies, though. Conversely, consumers with low protected values were willing to pay a premium for non-renewable energy. Overall, consumers with high education expressed a willingness to pay more for renewable energies, but consumers with high income and younger consumers did not. This research highlights the importance of shifting from fossil fuels to a low-carbon future by stressing the role of the factors that may affect consumer decision making.